Sub-cycle steering of the deprotonation of acetylene by intense few-cycle mid-infrared laser fields - Li, H.; Kling, Nora G.; Gaumnitz, T.; Burger, C.; Siemering, R.; Schoetz, J.; Liu, Qingcao; Ban, Loren; Pertot, Y.; Wu, J.; Azzeer, A. M.; De Vivie-Riedle, Regina; et al. (Optics Express, 2017)
Directional breaking of the C-H/C-D molecular bond is manipulated in acetylene (C2H2) and deuterated acetylene (C2D2) by waveform controlled few-cycle mid-infrared laser pulses with a central wavelength around 1.6 μm at an intensity of about 8 × 1013 W/cm2. The directionality of the deprotonation of acetylene is controlled by changing the carrier-envelope phase (CEP). The CEP-control can be attributed to the laser-induced superposition of vibrational modes, which is sensitive to the sub-cycle evolution of the laser waveform. Our experiments and simulations indicate that near-resonant, intense mid-infrared pulses permit a higher degree of control of the directionality of the reaction compared to those obtained in near-infrared fields, in particular for the deuterated species.
CRIS-Team Scopus Importer:2023-04-20